2019
DOI: 10.1029/2019jd030463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerosols on the Ice Cloud Properties Over the Tibetan Plateau

Abstract: With the highlight of environmental problems over the Tibetan Plateau (TP), aerosol pollution and the influence of this pollution on cloud properties are becoming a new area of research. Based on the aerosol index and cloud property parameters derived from satellite observations, in this study, the inconsistent effects of aerosols on ice cloud properties between daytime and nighttime over the TP are investigated. The results indicate that ice clouds are mainly distributed over the TP margin area, especially ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 80 publications
(99 reference statements)
1
41
0
Order By: Relevance
“…The annual mean snow albedo direct radiative forcing of BC may reach 2.9 W/m 2 [15], which will reduce the snow albedo and accelerate the melting of glaciers [16][17][18][19]. Moreover, the BC over the TP can affect the properties of cloud [20][21][22], precipitation [22][23][24] and the monsoon circulations [25].…”
Section: Introductionmentioning
confidence: 99%
“…The annual mean snow albedo direct radiative forcing of BC may reach 2.9 W/m 2 [15], which will reduce the snow albedo and accelerate the melting of glaciers [16][17][18][19]. Moreover, the BC over the TP can affect the properties of cloud [20][21][22], precipitation [22][23][24] and the monsoon circulations [25].…”
Section: Introductionmentioning
confidence: 99%
“…As observational evidence, Liu et al . () found that aerosols have a dominant influence on the daytime ice cloud droplet radius, nocturnal ice water path and ice cloud optical depth. Furthermore, Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…For Central Asia, Klein et al (2013) evaluated the cloud water using medium-resolution remote sensing data. Additionally, there are some studies on cloud properties over other regions, such as the Tibetan Plateau (Zhao et al, 2014;Hua et al, 2018;Liu et al, 2019a;2019b) and China (Liu et al, 2004;Shang et al, 2017) in CEA. Under the background of global warming, some researchers have focused heavily on cloud property responses.…”
Section: Introductionmentioning
confidence: 99%